2015
DOI: 10.1002/cyto.b.21326
|View full text |Cite
|
Sign up to set email alerts
|

Improved harmonization of eosin‐5‐maleimide binding test across different instruments and age groups

Abstract: The inclusion of footprint parameter will help in better standardization as well as implementation of this test across different age groups as well as different instruments. © 2015 International Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…There are still ongoing studies attempting to improve the utility of the EMA test. (43,46,53,61,62), while others use the mean fluorescence intensity obtained for EMAbound cells (63,64) or the EMA "footprint" (52,58). Despite these differences in presentation of EMA test results, it remains the most reliable screening test, with a relatively short time-around-time (TAT), high sensitivity, costeffectiveness and availability in laboratories equipped with even the most basic flow cytometer.…”
Section: Eosin-5'-maleimide Testmentioning
confidence: 99%
See 1 more Smart Citation
“…There are still ongoing studies attempting to improve the utility of the EMA test. (43,46,53,61,62), while others use the mean fluorescence intensity obtained for EMAbound cells (63,64) or the EMA "footprint" (52,58). Despite these differences in presentation of EMA test results, it remains the most reliable screening test, with a relatively short time-around-time (TAT), high sensitivity, costeffectiveness and availability in laboratories equipped with even the most basic flow cytometer.…”
Section: Eosin-5'-maleimide Testmentioning
confidence: 99%
“…, which is the position of EMA-bound RBCs in cytogram presenting side scatter versus EMA fluorescence channel, in order to allow better interpretation of the test(58). Finally Crisp et al demonstrated that a very small…”
mentioning
confidence: 99%
“…The guideline for a diagnosis of HS by EMA-flow cytometry in newborns suggests using red cells from healthy term newborns as controls [1, 7, 16]. However, two previous studies have shown that the EMA-flow cytometry results obtained from healthy newborns or neonatal cord blood red cells are not significantly different to those from adult red cells [18, 19]. These findings suggest that red cells from adults can be used as controls for a newborn study.…”
Section: Resultsmentioning
confidence: 99%
“…A flow cytometry‐based diagnosis of HS is still under research and development. Recently, Agarwal et al have published a paper that presents a new application of eosin‐5′‐maleimide test based on the analysis of EMA footprint, which indicates the position of EMA‐stained red blood cells in the cytogram with respect to EMA fluorescence and cells size (forward scatter). Similarly, a new test proposed by Won and Shu describes the flow cytometry‐based evaluation of osmotic fragility.…”
Section: Discussionmentioning
confidence: 99%